Representation of poverty in Akan proverbs - Asiedu Angelina (University of Cape Coast, 2024)
Research on proverbs have enough representation in the literature. In the case of Akan, most studies on proverbs focus on the representation of gender in proverbs. However, since proverbs are endowed with societal ideologies and past experiences, it is a great resource for examining many other concepts including poverty. This study, therefore, examines the representation of poverty in Akan proverbs drawing on Lakoff and Johnson‘s Conceptual Metaphor Theory. The objectives were to identify conceptual metaphors associated with proverbs about poverty, the experiential bases of these proverbs and the effects of these proverbs on the contemporary Akan. Data were collected from some Akan (Akuapem) consultants through interviews, Christaller‘s (1879) proverbs collection book and the media. Analysis of the data shows that the Akan represent poverty through their proverbs as disease, food, animate/human, omen and as a controller. These conceptual metaphors are derived from the historical and cultural system of the users. Finally, the study reveals that some of these proverbs still have relevance on the contemporary Akan whereas others are interpreted differently in recent times. This study contributes further empirical support to the Conceptual Metaphor Theory from the perspective of Akan.
xii,123p:,ill
Keywords: Akan Proverbs Poverty Conceptual Metaphors Ohia